PENGARUH KEPEMIMPINAN DEMOKRATIS TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (Studi Pada Pegawai Dewan Perwakilan Rakyat Daerah Kota Y) - Gigih Puja Priyagung; Nur Wening (MANAJEMEN DEWANTARA, 2020)
This study aims to examine the democratic leadership on employee performance with motivation as an intervening variable on employee of the DPRD Kota Y. The sample technique in this study used a census and collected 35 respondents. The techniques of collecting data using a questionnaire. Data analysis method used in the form of simple regression, multiple regression and path analysis. The results show that the democratic leadership have a positive and significant effect on motivation. Motivation has a positive and significant effect on employee performance., Democratic leadership has a positive and significant effect on employee performance. And motivation can mediate the relationship between democratic leadership and employee performance.Kata Kunci: Democratic leadership, motivation, employee prformance